Representasi Kekerasan Emosional pada Perempuan dalam Film “Story of Kale: When Someone's In Love” - Wahab, Annisa Patricia; Juwita, Rina; Nurliah, Nurliah; Agustian, Jaka Farih (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to analyze the representation of emotional violence against women in the film "Story of Kale: When Someone's in Love" by Angga Dwimas Sasongko. The research method used is a qualitative method with a semiotic analysis approach. The research results show that this film effectively depicts the dynamics of emotional violence through various cinematic elements. The female characters in this film often experience manipulation, emotional control and verbal abuse which are interpreted through semiotic signs. This representation provides deep insight into the complexity of emotional violence and its impact on victims. The film "Story of Kale: When Someone's in Love" has succeeded in becoming an example of media that represents emotional violence against women, and plays an important role in increasing public awareness and understanding of this issue.